Factors that affect the perceived health of adults with intellectual disability: A Western Australian study - Cocks, Errol; Thomson, Allyson; Thoresen, Stian; Parsons, R.; Rosenwax, Lorna (Taylor & Francis, 2017)
© 2017 Australasian Society for Intellectual Disability, Inc. Background Adults with intellectual disability (ID) experience poorer overall health than the wider population. Identification of personal, support service and lifestyle factors affecting health status will provide opportunities to improve health outcomes. Methods The study was a cross-sectional survey of adults with ID. Interviews were conducted between January and July 2013. Univariate and multivariate analyses were performed using self- or proxy-reported general health as the dependent variable. Results “Not good” health was independently associated with increasing age, financial hardship, smoking, and living in a home of their own. Physical exercise was inversely associated with not good health. Conclusions Subjective health may be improved by attention to the factors identified in this study. This could include closer monitoring of the health of people with ID as they age and if they live in a home of their own. Similarly, targeted programs promoting physical activity and smoking reduction could improve general health for adults with ID.